2022
DOI: 10.3389/fpsyt.2022.923938
|View full text |Cite
|
Sign up to set email alerts
|

Superior temporal gyrus functional connectivity predicts transcranial direct current stimulation response in Schizophrenia: A machine learning study

Abstract: Transcranial direct current stimulation (tDCS) is a promising adjuvant treatment for persistent auditory verbal hallucinations (AVH) in Schizophrenia (SZ). Nonetheless, there is considerable inter-patient variability in the treatment response of AVH to tDCS in SZ. Machine-learned models have the potential to predict clinical response to tDCS in SZ. This study aims to examine the feasibility of identifying SZ patients with persistent AVH (SZ-AVH) who will respond to tDCS based on resting-state functional connec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 82 publications
0
9
0
Order By: Relevance
“…Enhanced rsFC of the brain has been suggested as the mechanistic basis for the effects of other NIBS, such as tDCS and TMS, in depression, schizophrenia, and dementia [54][55][56][57]. An increase in rsFC in the default mode network (DMN) was also noted following PBM in stroke [22] and dementia [30].…”
Section: Discussionmentioning
confidence: 99%
“…Enhanced rsFC of the brain has been suggested as the mechanistic basis for the effects of other NIBS, such as tDCS and TMS, in depression, schizophrenia, and dementia [54][55][56][57]. An increase in rsFC in the default mode network (DMN) was also noted following PBM in stroke [22] and dementia [30].…”
Section: Discussionmentioning
confidence: 99%
“…Findings in schizophrenia with tDCS, a more portable method for neurostimulation, have also been examined in relation to fMRI, but data are preliminary. Functional connectivity of the superior temporal gyrus has been suggested as a potential prognostic marker for response to tDCS 321 . Separate studies focused on cognition have reported positive effects with tDCS in schizophrenia and associated changes in neural circuitry 322 .…”
Section: Neurostimulationmentioning
confidence: 99%
“…Interestingly, structural connectivity strength was not a relevant predictor. This could be explained by the fact that larger fibre tracts are often due to connecting larger brain regions without necessarily facilitating the spreading of neuromodulation effects throughout the network [29][30][31] www.nature.com/scientificreports/ individuals with schizophrenia to various treatments based on their rs-fMRI profiles 30 . Additionally, it has been employed to predict alterations in mood and cognitive functioning following transcranial direct current stimulation in patients diagnosed with major depression, utilizing rs-EEG data 31 .…”
Section: Tus Effects Could Be Anticipatedmentioning
confidence: 99%